Field Observations During the Fifth Microwave Water and Energy Balance Experiment (MicroWEX-5): from March 9 through May 26, 2006 - Joaquin Casanova; Fei Yan; Mi-young Jang; Juan Fernandez; Jasmeet Judge; Clint Slatton; Kai-Jen Calvin Tien; Tsu-yun Lin; Orlando Lanni; Larry Miller (EDIS)
Circular 1514, a 47-page illustrated report by Joaquin Casanova, Fei Yan, Mi-young Jang, Juan Fernandez, Jasmeet Judge, Clint Slatton, Kai-Jen Calvin Tien, Tzu-yun Lin, Orlando Lanni, and Larry Miller, presents the results of experiments using microwave remote sensing to determine root-zone soil moisture at UF/IFAS PSREU. Published by the UF Department of Agricultural and Biological Engineering, May 2007.